Construyendo nuevas visiones sobre Transferencia de tecnología y cooperación sur-sur. La experiencia del instituto nacional de tecnología industrial (inti) - Muset, Graciela; Kern, Alejandra S.; Suárez, M. Eugenia (Revista Española de Desarrollo y Cooperación, 2023)
Cooperation with countries of equal or lower level of development has been a constant in the external action of the INTI, In the beginning, the actions were designed to meet specific and concrete demands submitted by the demanding countries. Since 2002, changes in Argentina and, as a consequence, in the INTI, have created new bases and concepts that today supports this cooperation.